2015
DOI: 10.5539/ijb.v7n3p18
|View full text |Cite
|
Sign up to set email alerts
|

Population Diversity of Leptosphaeria maculans in Australia

Abstract: The fungal pathogen Leptosphaeria maculans, causal agent of blackleg disease, is a primary cause of canola (Brassica napus) crop loss in Australia. Expanding our knowledge of the occurrence of this pathogen in Australia will provide valuable insights into developing methods of resistance against it. In this study, we examine the population diversity of L. maculans in Australia using single nucleotide polymorphisms (SNPs). An Illumina GoldenGate 384 SNP assay was developed and used to genotype 59 blackleg isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The overall method of genetic spread of L. maculans in the environment is yet to be elucidated, as the latest studies have shown contrasting population structures in different regions (Dilmaghani et al, 2012, Travadon et al, 2011. A recent diversity analysis by Patel et al (2015) indicates that the L. maculans population in Australia is panmictic, with high rate of sexual reproduction and evolutionary diversification within fungal populations.…”
Section: Maculans Genetics and Genomicsmentioning
confidence: 99%
“…The overall method of genetic spread of L. maculans in the environment is yet to be elucidated, as the latest studies have shown contrasting population structures in different regions (Dilmaghani et al, 2012, Travadon et al, 2011. A recent diversity analysis by Patel et al (2015) indicates that the L. maculans population in Australia is panmictic, with high rate of sexual reproduction and evolutionary diversification within fungal populations.…”
Section: Maculans Genetics and Genomicsmentioning
confidence: 99%
“…Previous work (Chapter 3; Rouxel et al, 2011;Zander et al, 2013;Grandaubert et al, 2014b;Patel et al, 2015) has led us to understand that the Australian blackleg population is highly diverse.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Dilmaghani et al (2012) proposed from minisatellite marker results that two genetically different populations of blackleg are present in Western Canada. Zander et al (2013) conducted a small scale population diversity study using SNPs, whose successful results were used as a foundation for the large-scale study described in Patel et al (2015) (Chapter 3).…”
Section: Population Diversitymentioning
confidence: 99%
See 2 more Smart Citations